2010
DOI: 10.1111/j.1095-8312.2010.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

On the role of sexual selection in ecological divergence: a test of body-size assortative mating in the eastern newt Notophthalmus viridescens

Abstract: Speciation processes initiated by divergent selection often fail to complete; yet, how sexual selection is involved in the progress of ecological speciation is rarely understood. Intraspecific body-size variation affects mate preference and male-male competition, which can consequently lead to assortative mating based on body size. In the present study, we tested the importance of body size difference in the potential of assortative mating between the two eastern newt subspecies, larger Notophthalmus viridesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 79 publications
(148 reference statements)
2
7
0
Order By: Relevance
“…Subspecies of N. viridescens represent ecologically distinct groups that have arisen rapidly in the last 10,000 years via niche divergence during range expansion from glacial refugia (Takahashi et al., ), yet little is known about where these subspecies lie on the speciation continuum. Although there is some evidence of assortative mating by body size, consistent with our finding of a large size component to among‐species and subspecies divergence, prezygotic reproductive isolation appears to be incomplete between some subspecies (Takahashi et al., ). Although lack of complete speciation in this clade does not effect the interpretation of our data, as subspecies do represent ecologically‐ and phenotypically diverged entities (Takahashi et al., ), future work examining the extent of pre‐ and postzygotic reproductive isolation in N. viridescens , experimental assessment of divergent selection and variation in sexual dimorphism across subspecies ranges would be informative.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Subspecies of N. viridescens represent ecologically distinct groups that have arisen rapidly in the last 10,000 years via niche divergence during range expansion from glacial refugia (Takahashi et al., ), yet little is known about where these subspecies lie on the speciation continuum. Although there is some evidence of assortative mating by body size, consistent with our finding of a large size component to among‐species and subspecies divergence, prezygotic reproductive isolation appears to be incomplete between some subspecies (Takahashi et al., ). Although lack of complete speciation in this clade does not effect the interpretation of our data, as subspecies do represent ecologically‐ and phenotypically diverged entities (Takahashi et al., ), future work examining the extent of pre‐ and postzygotic reproductive isolation in N. viridescens , experimental assessment of divergent selection and variation in sexual dimorphism across subspecies ranges would be informative.…”
Section: Discussionsupporting
confidence: 88%
“…The direction of maximum divergence between the sexes, s max (green dashed arrows) defined as the first eigenvector of the covariance matrix S of canonical coefficients from taxon-specific canonical discriminant analyses on the sexes, correlates strongly with the γ max (black arrows), the direction of maximum disruptive selection measured in N. v. viridescens. The same qualitative conclusions were obtained with the mean vector of canonical coefficients (solid green arrows (Takahashi & Parris, 2008;Takahashi, Takahashi, & Parris, 2010;Takahashi et al, 2011). Second, the correspondence between withinspecies estimates of SA disruptive natural selection and divergence in sexual dimorphism across species indicates that sexual dimorphism in head shape in Notophthalmus may in part represent the outcome of within-pond resource competition.…”
Section: Notophthalmussupporting
confidence: 61%
See 1 more Smart Citation
“…Our current understanding of adaptive radiation in anoles is based on a paradigm of ecological and allopatric speciation due to evolutionary change in continuously varying traits driven by interspecific competition and niche divergence. The existence of intraspecific dimorphisms in A. nebulosus and A. agassizi raises the possibility that sympatric speciation, driven by intraspecific competition, predation or sexual selection, may have played a role in the origin of new Anolis species, as is apparently the case in a variety of other taxa (Knudsen et al ., ; Huber et al ., ; Takahashi, Takahashi & Parris, ; Winkelmann et al ., ). Butler et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that male newts prefer larger females because of fecundity advantages (Verrell, 1985(Verrell, , 1986, and larger males gain prior access to larger females by winning male-male competition (Verrell, 1986;Gabor et al, 2000), suggesting possibility of body-size assortative mating. However, a recent study showed that body-size assortative mating is probably not occurring (Takahashi et al, 2010). While larger males of N. v. viridescens gain prior access to larger females of their own kind, males of smaller subspecies still have chances to mate with female N. v. viridescens through sexual interference during spermatophore deposition of larger males.…”
Section: Effect Of Glaciations and The Origin Of Ecological Niche DIVmentioning
confidence: 98%